Trait emotional intelligence profiles of professionals in Kuwait - Hasan, Nasser N.; Petrides, Konstantinos V.; Hull, Laura; Hadi, Fawziyah (Frontiers in Psychology, 2023)
Trait emotional intelligence concerns people’s perceptions of their emotional world. Our aims for this study are to examine (a) the trait emotional intelligence (EI) profiles across different professions in Kuwait; (b) the incremental validity of trait EI in predicting job performance; and (c) the relationship between trait EI, job attitudes, and job performance. The sample comprised 314 professionals in Kuwait in seven different professions: Bankers, Engineers, Healthcare providers, Lawyers, Military, Policemen, and Teachers. Firstly, the results showed that the Military scored the lowest global trait emotional intelligence and three of four factors. Secondly, the results showed that global trait EI incrementally predicted job performance over job attitudes in Policemen and Engineers but not in other professions. Lastly, the results showed that job attitudes partially mediated the relationship between trait EI and job performance. These findings call for the importance of trait emotional intelligence trainings for professionals in Kuwait as it affects important job-related variables. The limitations of this study and the directions for future studies have been discussed.